(untitled) (Research, Society and Development, 2021)
The aim of the present study was to investigate the real impact of Diabetes Mellitus on the clinical outcome of patients affected by COVID-19. This is an integrative literature review carried out in April 2021, analyzing publications indexed in the Science Direct and PubMed databases, adopting retrospective cohort studies published between the years 2020 and 2021, in the English language. To eliminate duplicate studies, the Mendeley Desktop 1.19.8 bibliographic reference manager was used. Of the 10 selected studies, 5 of them were carried out in China, while the remaining 5 took place in Iran, England, Belgium and the United States, carried out between the months of January and July 2020. The results demonstrated a strong impact of Diabetes Mellitus on a worst clinical outcome in hospitalizations due to COVID-19. In the present review, the significant impact that the pathogenesis of DM has on the different cells inherent to the immune system was evidenced, in addition to the increased risk of the need for admission to the ICU and the use of respiratory support to contain the worsening of the disease. However, studies of greater precision, population control and / or comorbidities are necessary for a better understanding of the real losses of the association between DM and COVID-19.